Application Design of Web-based Computer Laboratory Inventory and Maintenance System at SMK Bhakti Anindya - Reza Syafrizal; Sarmuni Sarmuni; Rizki Aibar (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
This paper describes a problem in computer laboratory maintenance and inventory. Inventory of goods in Every company or institution always has a connection with the data management process of goods / equipment owned by the company. In addition to inventory, maintenance is also very necessary in order to keep company assets under control, safe, and always maintained. For this reason, an Inventory Information System is needed as well as a maintenance system in managing the data. The results of this design are focused on managing information about the management of goods and several aspects regarding the maintenance of goods, especially in the computer laboratory of SMK Bhakti Anindya. With the implementation of the maintenance information system and laboratory inventory at Bhakti Anindya Vocational School, data management and equipment maintenance will be better. Tulisan ini menjelaskan mengenai sebuah permasalahan dalam perawatan dan inventaris laboratorium komputer. Inventarisasi barang dalam Setiap perusahaan atau sebuah lembaga selalu memiliki keterkaitan dengan proses pengelolaan data barang / peralatan yang di miliki oleh perusahaan tersebut. Disamping inventarisasi, hal perawatan juga sangat diperlukan demi menjaga agar aset perusahaan terkontrol, aman, dan selalu terawat. Untuk itulah di butuhkan suatu Sistem Informasi Inventaris sekaligus sistem perawatannya dalam mengelola data tersebut. Hasil dari rancang bangun ini dititik beratkan pada pengelolaan informasi tentang pengelolaan barang dan beberapa aspek mengenai perawatan barang terutama pada bagian laboratorium komputer SMK Bhakti Anindya. Dengan diimplementasikannya sistem informasi Perawatan dan inventaris laboratorium di SMK Bhakti Anindya, pengelolaan data barang dan perawatan alat akan lebih baik.